A low dielectric constant borate microwave dielectric ceramic and preparation method thereof
By adopting the high-temperature solid-phase reaction method with a chemical composition of SrSn(BO3)2, a low-dipela-constant borate microwave dielectric ceramic with a dielectric constant of 5.42~6.12 and a quality factor of 22142GHz~32618GHz was prepared, which solved the problem of limited market share of low-dipela-constant dielectric ceramics in the prior art, and realized the preparation of high-performance ceramics, which is suitable for high-data transmission scenarios.
Patent Information
- Application Number
- CN202310182515.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-24
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-02-24
AI Technical Summary
The medium and low dielectric constant dielectric ceramics in the prior art have not yet formed a scale and have limited market share, which cannot meet the communication technology needs of high data transmission rates and low network latency.
The chemical composition of SrSn(BO3)2 was used to synthesize low-dielectric constant borate microwave dielectric ceramics by high-temperature solid phase reaction method, with dielectric constants ranging from 5.42 to 6.12 and quality factors ranging from 22142GHz to 32618GHz. The preparation methods include presintering, wet ball milling, granulation and sintering treatment.
It realizes high-performance preparation of low-dielectric constant borate microwave dielectric ceramics, with lower dielectric constant and higher quality factor, and is suitable for high data transmission scenarios such as 5G communication.
Smart Images

Figure CN116332628B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of preparation of electronic information functional materials, and in particular to a low dielectric constant borate microwave dielectric ceramic and a preparation method thereof. Background Art
[0002] The main development direction of various communication technologies with high data transmission rates and low network latency is the cornerstone of society's transformation to digitalization, networking, and intelligence, and has important strategic significance in both military and civilian fields. Communication technologies with high data transmission rates and low network latency require that the delay time of each device in the equipment in response to the signal is as short as possible. According to electromagnetic field theory and electromagnetic propagation formulas, the lower the dielectric constant, the shorter the signal delay time of the radio wave in the carrier medium. For this reason, microwave ceramics, which are key carrier media for devices such as antennas and substrates, must have the lowest possible dielectric constant. For example, microwave substrates widely used in 5G communications require a dielectric constant of less than 15.
[0003] At present, low dielectric constant dielectric ceramics have not yet formed a scale and the market share is very limited. Therefore, this field urgently needs to develop a new type of microwave dielectric ceramic material to enrich the application needs in the low dielectric constant communication environment. Summary of the invention
[0004] The present invention discloses a low dielectric constant borate microwave dielectric ceramic and a preparation method thereof. The low dielectric constant borate microwave dielectric ceramic prepared by the preparation method has a dielectric constant of 5.42 to 6.12, a temperature coefficient of -48.31 ppm / °C to -53.37 ppm / °C, and a quality factor of 22142 GHz to 32618 GHz.
[0005] According to a first aspect of an embodiment of the present disclosure, a low dielectric constant borate microwave dielectric ceramic is provided, wherein the chemical composition expression of the low dielectric constant borate microwave dielectric ceramic is SrSn(BO3)2, the dielectric constant of the low dielectric constant borate microwave dielectric ceramic is 5.42-6.12, the quality factor of the low dielectric constant borate microwave dielectric ceramic is 22142GHz-32618GHz, and the resonant frequency temperature coefficient of the low dielectric constant borate microwave dielectric ceramic is -48.31ppm / ℃-53.37ppm / ℃.
[0006] According to a second aspect of an embodiment of the present disclosure, a method for preparing a low dielectric constant borate microwave dielectric ceramic is provided, which is used to prepare the low dielectric constant borate microwave dielectric ceramic as described in the first aspect, and the method comprises:
[0007] S1. According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed and mixed in a molar ratio of 1:1:1.5 to obtain a mixed raw material;
[0008] S2, pre-sintering the mixed raw material to obtain a pre-sintered raw material;
[0009] S3, wet-milling the pre-sintered raw material and anhydrous ethanol to obtain a slurry-like raw material;
[0010] S4, drying the slurry-like raw material to constant weight to obtain a dry mixed material;
[0011] S5, adding the PVA aqueous solution to the sieved and dispersed mixture, mixing, granulating, and pressing to form a ceramic body;
[0012] S6, performing a debinding treatment on the ceramic green body and then performing a sintering treatment to obtain the low dielectric constant borate microwave dielectric ceramic.
[0013] Preferably, the pre-sintering of the mixed raw material comprises:
[0014] The mixed raw materials were placed in a sintering furnace, heated to 1000° C. at a heating rate of 5° C. / min and kept at that temperature for 10 hours to complete pre-sintering.
[0015] Preferably, the wet ball milling of the pre-sintered raw material and anhydrous ethanol to obtain a slurry raw material comprises:
[0016] The pre-sintered raw material and anhydrous ethanol are added into a polytetrafluoroethylene ball mill containing zirconium balls at a mass ratio of 1:1.5 to mix them to obtain an initial slurry raw material;
[0017] The initial slurry-like raw material is put into a planetary ball mill and ball-milled for 12 hours to obtain the slurry-like raw material.
[0018] Preferably, the step of drying the slurry-like raw material to a constant weight to obtain a dry mixed material comprises:
[0019] The slurry-like raw material was placed in a blast drying oven at 70° C. and dried for 12 hours to obtain the mixed material.
[0020] Preferably, the step of adding the PVA aqueous solution to the sieved and dispersed mixed material, mixing, granulating, and pressing to form a ceramic body comprises:
[0021] The mixed material is passed through an 80-mesh sieve for dispersion treatment.
[0022] Preferably, the mass fraction of the PVA aqueous solution is 5%, and the added amount of the PVA aqueous solution is 8wt% of the mass of the mixed material.
[0023] Preferably, the ceramic body has a diameter of 12 mm and a height of 6 mm.
[0024] Preferably, the debinding treatment of the ceramic green body followed by sintering treatment comprises:
[0025] The ceramic green body is placed on a pad and then placed in a high-temperature furnace, and the temperature is increased to 550° C. at a heating rate of 5° C. / min and kept at this temperature for 3 hours to complete the debinding treatment.
[0026] Preferably, the debinding treatment of the ceramic green body followed by sintering treatment comprises:
[0027] The ceramic green body after the debinding treatment is placed in a sintering furnace, and the temperature is raised to 1100° C. to 1200° C. at a heating rate of 5° C. / min and kept at this temperature for 8 hours to complete the sintering treatment.
[0028] The technical solution provided by the embodiments of the present disclosure brings at least the following beneficial effects:
[0029] The low dielectric constant borate microwave dielectric ceramics provided by the embodiments of the present disclosure have a simple preparation process, and the powder synthesized by the high temperature solid phase reaction method has a high purity. Compared with the existing microwave dielectric ceramic materials, the low dielectric constant borate microwave dielectric ceramics prepared have excellent performance, a lower dielectric constant, and a higher quality factor. The dielectric constant is 5.42 to 6.12, the temperature coefficient is -48.31ppm / ℃ to -53.37ppm / ℃, and the quality factor is 22142GHz to 32618GHz.
[0030] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings herein are incorporated into and constitute a part of the specification, illustrate embodiments consistent with the present disclosure, and together with the description are used to explain the principles of the present disclosure, and do not constitute improper limitations on the present disclosure.
[0032] Figure 1 It is a schematic flow chart of a method for preparing a low dielectric constant borate microwave dielectric ceramic according to an exemplary embodiment.
[0033] Figure 2 The figure is an X-ray diffraction pattern of a low dielectric constant borate microwave dielectric ceramic according to an exemplary embodiment.
[0034] Figure 3 is a crystal structure diagram of a low dielectric constant borate microwave dielectric ceramic according to an exemplary embodiment.
[0035] Figure 4 is a SEM image of a low dielectric constant borate microwave dielectric ceramic according to an exemplary embodiment.
[0036] Figure 5 is a dielectric property diagram of a low dielectric constant borate microwave dielectric ceramic according to an exemplary embodiment. DETAILED DESCRIPTION
[0037] In order to enable ordinary persons in the art to better understand the technical solutions of the present disclosure, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the accompanying drawings.
[0038] It should be noted that the terms "first", "second", etc. in the specification and claims of the present disclosure and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present disclosure described herein can be implemented in an order other than those illustrated or described herein. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present disclosure. Instead, they are merely examples of devices and methods consistent with some aspects of the present disclosure as detailed in the appended claims.
[0039] The embodiment of the present disclosure provides a low dielectric constant borate microwave dielectric ceramic, the chemical composition expression of the low dielectric constant borate microwave dielectric ceramic is SrSn(BO3)2, the dielectric constant is 5.42~6.12, the quality factor is 22142GHz~32618GHz (f=15.68GHz), and the resonant frequency temperature coefficient is -48.31ppm / ℃~-53.37ppm / ℃.
[0040] The present disclosure also provides a method for preparing a low dielectric constant borate microwave dielectric ceramic. Figure 1 As shown, the method comprises the following steps:
[0041] S1. According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed and mixed in a molar ratio of 1:1:1.5 to obtain a mixed raw material.
[0042] In this embodiment, SrCO3, SnO2 and B2O3 are all McLean chemical pure reagents, and when weighing B2O3, its mass is 15wt% excessive, which can compensate for the boron element volatilized at high temperature. Afterwards, the weighed B2O3, SnO2 and SrCO3 raw materials can be put into a polytetrafluoroethylene ball mill and mixed evenly.
[0043] S2, pre-sintering the mixed raw material to obtain a pre-sintered raw material.
[0044] In this embodiment, the mixed raw material can be placed in a sintering furnace, heated to 1000° C. at a heating rate of 5° C. / min and kept warm for 10 hours to complete pre-sintering, so as to obtain a pre-sintered raw material.
[0045] S3. Wet-milling the pre-sintered raw material with anhydrous ethanol to obtain a slurry-like raw material.
[0046] In this embodiment, the pre-sintered raw material and anhydrous ethanol can be added to a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5 and mixed to obtain an initial slurry raw material; then, the initial slurry raw material is placed in a planetary ball mill and ball-milled for 12 hours to obtain a slurry raw material.
[0047] S4. Dry the slurry raw material to constant weight to obtain a dry mixed material.
[0048] In this embodiment, the slurry raw material can be placed in a blast drying oven at 70° C. and dried for 12 hours to obtain a mixture. The mixture in this embodiment is SrSn(BO3)2 powder.
[0049] S5. Add the PVA aqueous solution to the sieved and dispersed mixture, mix, granulate, and press to form a ceramic body.
[0050] In this embodiment, the mixed material can be dispersed through an 80-mesh sieve, and then the PVA aqueous solution is added to the dispersed mixed material and mixed for granulation. In practical applications, the mass fraction of the PVA aqueous solution is 5%, and the amount of the PVA aqueous solution added is 8wt% of the mass of the mixed material.
[0051] In this embodiment, the diameter of the ceramic body is 12 mm and the height is 6 mm.
[0052] S6. After debinding the ceramic body, sintering is performed to obtain a low dielectric constant borate microwave dielectric ceramic.
[0053] In this embodiment, the ceramic body can be placed on a pad and then placed in a high-temperature furnace, and the temperature is increased to 550° C. at a heating rate of 5° C. / min and kept for 3 hours to complete the debinding process.
[0054] After the debinding treatment of the ceramic green body is completed, the ceramic green body after the debinding treatment can be placed in a sintering furnace, and the temperature is increased to 1100° C. to 1200° C. at a heating rate of 5° C. / min and kept at this temperature for 8 hours to complete the sintering treatment.
[0055] In practical applications, the temperatures for sintering the ceramic body may include 1100°C, 1125°C, 1150°C, 1175°C and 1200°C.
[0056] The preparation method of the low dielectric constant borate microwave dielectric ceramic disclosed in the present invention is further described below through specific examples.
[0057] Example 1
[0058] The method for preparing the low dielectric constant borate microwave dielectric ceramic of this embodiment comprises the following steps:
[0059] (1) According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed in a molar ratio of 1:1:1.5, and the weighed B2O3, SnO2 and SrCO3 raw materials are placed in a polytetrafluoroethylene ball mill and mixed evenly to obtain a mixed raw material.
[0060] (2) The mixed raw material is placed in a sintering furnace, and the temperature is raised to 1000° C. at a heating rate of 5° C. / min and kept at this temperature for 10 hours to complete pre-sintering, thereby obtaining a pre-sintered raw material.
[0061] (3) The pre-sintered raw material and anhydrous ethanol were added into a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5, respectively, and the mixed raw materials were placed in a planetary ball mill and ball-milled for 12 hours to obtain a slurry raw material.
[0062] (4) The slurry raw material was placed in a forced air drying oven at 70°C and dried for 12 hours to obtain dry SrSn(BO3)2 powder.
[0063] (5) The dried SrSn(BO3)2 powder was sieved through an 80-mesh sieve, added with a PVA aqueous solution, mixed, and granulated, and pressed to form a ceramic body with a diameter of 12 mm and a height of 6 mm. The mass fraction of the PVA aqueous solution was 5%, and the amount of the PVA aqueous solution added was 8 wt% of the mass of the mixture.
[0064] (6) The ceramic body is placed on a pad and then placed in a high-temperature furnace. The temperature is increased to 550°C at a heating rate of 5°C / min and kept at this temperature for 3 hours to complete the debinding treatment.
[0065] (7) The ceramic green body after debinding treatment is placed in a sintering furnace, heated to 1100°C at a heating rate of 5°C / min and kept at this temperature for 8 hours to complete the sintering treatment, thereby obtaining a low dielectric constant borate microwave dielectric ceramic with a dielectric property of: ε r =5.79, Q×f=22142GHz (f=15.68GHz), τ f =-53.37ppm / ℃.
[0066] Example 2
[0067] The method for preparing the low dielectric constant borate microwave dielectric ceramic of this embodiment comprises the following steps:
[0068] (1) According to the chemical formula of SrSn(Bo3)2, SrCO3, SnO2 and B2O3 raw materials are weighed in a molar ratio of 1:1:1.5, and the weighed B2O3, SnO2 and SrCO3 raw materials are placed in a polytetrafluoroethylene ball mill and mixed evenly to obtain a mixed raw material.
[0069] (2) The mixed raw material is placed in a sintering furnace, and the temperature is raised to 1000° C. at a heating rate of 5° C. / min and kept at this temperature for 10 hours to complete pre-sintering, thereby obtaining a pre-sintered raw material.
[0070] (3) The pre-sintered raw material and anhydrous ethanol were added into a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5, respectively, and the mixed raw materials were placed in a planetary ball mill and ball-milled for 12 hours to obtain a slurry raw material.
[0071] (4) The slurry raw material was placed in a forced air drying oven at 70°C and dried for 12 hours to obtain dry SrSn(BO3)2 powder.
[0072] (5) The dried SrSn(BO3)2 powder was sieved through an 80-mesh sieve, added with a PVA aqueous solution, mixed, and granulated, and pressed to form a ceramic body with a diameter of 12 mm and a height of 6 mm. The mass fraction of the PVA aqueous solution was 5%, and the amount of the PVA aqueous solution added was 8 wt% of the mass of the mixture.
[0073] (6) The ceramic body is placed on a pad and then placed in a high-temperature furnace. The temperature is increased to 550°C at a heating rate of 5°C / min and kept at this temperature for 3 hours to complete the debinding treatment.
[0074] (7) The ceramic body after debinding treatment is placed in a sintering furnace, heated to 1125°C at a heating rate of 5°C / min and kept at this temperature for 8 hours to complete the sintering treatment, thereby obtaining a low dielectric constant borate microwave dielectric ceramic with dielectric properties of: ε r =5.63, Q×f=26945GHz (f=15.68GHz), τ f =-50.66ppm / ℃.
[0075] Example 3
[0076] The method for preparing the low dielectric constant borate microwave dielectric ceramic of this embodiment comprises the following steps:
[0077] (1) According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed in a molar ratio of 1:1:1.5, and the weighed B2O3, SnO2 and SrCO3 raw materials are placed in a polytetrafluoroethylene ball mill and mixed evenly to obtain a mixed raw material.
[0078] (2) The mixed raw material is placed in a sintering furnace, and the temperature is raised to 1000° C. at a heating rate of 5° C. / min and kept at this temperature for 10 hours to complete pre-sintering, thereby obtaining a pre-sintered raw material.
[0079] (3) The pre-sintered raw material and anhydrous ethanol were added into a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5, respectively, and the mixed raw materials were placed in a planetary ball mill and ball-milled for 12 hours to obtain a slurry raw material.
[0080] (4) The slurry raw material was placed in a forced air drying oven at 70°C and dried for 12 hours to obtain dry SrSn(BO3)2 powder.
[0081] (5) The dried SrSn(BO3)2 powder was sieved through an 80-mesh sieve, added with a PVA aqueous solution, mixed, and granulated, and pressed to form a ceramic body with a diameter of 12 mm and a height of 6 mm. The mass fraction of the PVA aqueous solution was 5%, and the amount of the PVA aqueous solution added was 8 wt% of the mass of the mixture.
[0082] (6) The ceramic body is placed on a pad and then placed in a high-temperature furnace. The temperature is increased to 550°C at a heating rate of 5°C / min and kept at this temperature for 3 hours to complete the debinding treatment.
[0083] (7) The ceramic body after debinding treatment is placed in a sintering furnace, and the temperature is raised to 1150°C at a heating rate of 5°C / min and kept at this temperature for 8 hours to complete the sintering treatment, thereby obtaining a low dielectric constant borate microwave dielectric ceramic with the dielectric properties of: ε r =5.42, Q×f=32618GHz (f=15.68GHz), τ f =-48.28ppm / ℃.
[0084] Example 4
[0085] The method for preparing the low dielectric constant borate microwave dielectric ceramic of this embodiment comprises the following steps:
[0086] (1) According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed in a molar ratio of 1:1:1.5, and the weighed B2O3, SnO2 and SrCO3 raw materials are placed in a polytetrafluoroethylene ball mill and mixed evenly to obtain a mixed raw material.
[0087] (2) The mixed raw material is placed in a sintering furnace, and the temperature is raised to 1000° C. at a heating rate of 5° C. / min and kept at this temperature for 10 hours to complete pre-sintering, thereby obtaining a pre-sintered raw material.
[0088] (3) The pre-sintered raw material and anhydrous ethanol were added into a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5, respectively, and the mixed raw materials were placed in a planetary ball mill and ball-milled for 12 hours to obtain a slurry raw material.
[0089] (4) The slurry raw material was placed in a forced air drying oven at 70°C and dried for 12 hours to obtain dry SrSn(BO3)2 powder.
[0090] (5) The dried SrSn(BO3)2 powder was sieved through an 80-mesh sieve, added with a PVA aqueous solution, mixed, and granulated, and pressed to form a ceramic body with a diameter of 12 mm and a height of 6 mm. The mass fraction of the PVA aqueous solution was 5%, and the amount of the PVA aqueous solution added was 8 wt% of the mass of the mixture.
[0091] (6) The ceramic body is placed on a pad and then placed in a high-temperature furnace. The temperature is increased to 550°C at a heating rate of 5°C / min and kept at this temperature for 3 hours to complete the debinding treatment.
[0092] (7) The ceramic body after debinding treatment was placed in a sintering furnace, heated to 1175°C at a heating rate of 5°C / min and kept at this temperature for 8 hours to complete the sintering treatment, thereby obtaining a low dielectric constant borate microwave dielectric ceramic with dielectric properties of: ε r =5.95, Q×f=28541GHz (f=15.68GHz), τ f =-48.31ppm / ℃.
[0093] Example 5
[0094] The method for preparing the low dielectric constant borate microwave dielectric ceramic of this embodiment comprises the following steps:
[0095] (1) According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed in a molar ratio of 1:1:1.5, and the weighed B2O3, SnO2 and SrCO3 raw materials are placed in a polytetrafluoroethylene ball mill and mixed evenly to obtain a mixed raw material.
[0096] (2) The mixed raw material is placed in a sintering furnace, and the temperature is raised to 1000° C. at a heating rate of 5° C. / min and kept at this temperature for 10 hours to complete pre-sintering, thereby obtaining a pre-sintered raw material.
[0097] (3) The pre-sintered raw material and anhydrous ethanol were added into a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5, respectively, and the mixed raw materials were placed in a planetary ball mill and ball-milled for 12 hours to obtain a slurry raw material.
[0098] (4) The slurry raw material was placed in a forced air drying oven at 70°C and dried for 12 hours to obtain dry SrSn(BO3)2 powder.
[0099] (5) The dried SrSn(BO302) powder was passed through an 80-mesh sieve, added with a PVA aqueous solution, mixed, and granulated, and pressed to form a ceramic body with a diameter of 12 mm and a height of 6 mm. The mass fraction of the PVA aqueous solution was 5%, and the amount of the PVA aqueous solution added was 8 wt% of the mass of the mixture.
[0100] (6) The ceramic body is placed on a pad and then placed in a high-temperature furnace. The temperature is increased to 550°C at a heating rate of 5°C / min and kept at this temperature for 3 hours to complete the debinding treatment.
[0101] (7) The ceramic body after debinding treatment is placed in a sintering furnace, heated to 1200°C at a heating rate of 5°C / min and kept at this temperature for 8 hours to complete the sintering treatment, thereby obtaining a low dielectric constant borate microwave dielectric ceramic with a dielectric property of: ε r =6.12, Q×f=23054GHz (f=15.68GHz), τ f =-50.42ppm / ℃.
[0102] Figure 2 The X-ray diffraction patterns of SrSn(BO3)2 samples sintered at different temperatures (1100-1200℃) are shown in the figure. They belong to the trigonal crystal system with a space group of R3 (No.148), which is consistent with the ICSD#74-2213 card and has no other impurity peaks, indicating that a pure phase SrSn(BO3)2 ceramic has been formed.
[0103] Figure 3 It can be seen that the crystal structure of SrSn(BO3)2 ceramics is composed of a layered structure of [SrO6] octahedrons, [SnO6] octahedrons and [BO3] planar triangles (B is located in the center of the equilateral triangle composed of three oxygen atoms); its unit cell structure is that multiple [SrO6] octahedra form the first layer, and [SnO6] octahedra form the second layer, and the two layers are connected by shared oxygen atoms at the vertices.
[0104] Figure 4The microstructure of SrSn(BO3)2 ceramics at different sintering temperatures (1100-1200℃) is shown. (a) is the microstructure of SrSn(BO3)2 ceramics at a sintering temperature of 1100℃, (b) is the microstructure of SrSn(BO3)2 ceramics at a sintering temperature of 1125℃, (c) is the microstructure of SrSn(BO3)2 ceramics at a sintering temperature of 1150℃, (d) is the microstructure of SrSn(BO3)2 ceramics at a sintering temperature of 1175℃, and (e) is the microstructure of SrSn(BO3)2 ceramics at a sintering temperature of 1200℃. It can be seen that with the increase of temperature, the micropores between the grains in Figures (a) to (c) gradually disappear, and the crystallinity improves. SrSn(BO3)2 ceramics have good microstructure at 1150℃, but as the temperature continues to rise, the grain boundaries become blurred from Figure (d) to (e), the grains grow in uneven sizes, and some grains grow abnormally.
[0105] Figure 5 The dielectric properties of SrSn(BO3)2 ceramics are shown in Figure 2. The quality factor Q×f value decreases first and then increases, reaching the minimum value at 1100℃ and the maximum value at 1150℃, while the dielectric constant has the opposite trend. Figure 4 ) has the most uniform grains and the least micropores at 1150℃, which indicates that both micropores and grain size will affect the dielectric properties of ceramics.
[0106] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. The present disclosure is intended to cover any variations, uses or adaptations of the present disclosure that follow the general principles of the present disclosure and include common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The description and examples are to be considered exemplary only, and the true scope and spirit of the present disclosure are indicated by the following claims.
[0107] It should be understood that the present disclosure is not limited to the exact structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present disclosure is limited only by the appended claims.
Claims
1. A method for preparing low dielectric constant borate microwave dielectric ceramics, characterized in that: The method comprises: S1. According to the chemical formula of SrSn(BO3)2, SrCO3, SnO2 and B2O3 raw materials are weighed and mixed in a molar ratio of 1:1:1.5 to obtain a mixed raw material; S2, pre-sintering the mixed raw material to obtain a pre-sintered raw material; S3, wet-milling the pre-sintered raw material and anhydrous ethanol to obtain a slurry raw material, comprising: adding the pre-sintered raw material and anhydrous ethanol to a polytetrafluoroethylene ball mill containing zirconium balls in a mass ratio of 1:1.5, respectively, and mixing them to obtain an initial slurry raw material; The initial slurry-like raw material is placed in a planetary ball mill and ball-milled for 12 hours to obtain the slurry-like raw material; S4, drying the slurry-like raw material to a constant weight to obtain a dry mixed material, comprising: The slurry-like raw material is placed in a blast drying oven at 70° C. and dried for 12 hours to obtain the mixed material; S5, adding the PVA aqueous solution to the sieved and dispersed mixture, mixing, granulating, and pressing to form a ceramic body; S6, debinding the ceramic green body, comprising: placing the ceramic green body on a pad and then placing it in a high-temperature furnace, heating the temperature to 550° C. at a heating rate of 5° C. / min and maintaining the temperature for 3 hours to complete the debinding treatment; After debinding, sintering treatment is performed to obtain the low dielectric constant borate microwave dielectric ceramic, wherein the dielectric constant of the low dielectric constant borate microwave dielectric ceramic is 5.42-6.12, the quality factor of the low dielectric constant borate microwave dielectric ceramic is 22142 GHz-32618 GHz, and the resonant frequency temperature coefficient of the low dielectric constant borate microwave dielectric ceramic is -48.31 ppm / °C-53.37 ppm / °C; The crystal structure of SrSn(BO3)2 ceramics is a layered structure composed of [SrO6] octahedron, [SnO6] octahedron and [BO3] plane triangle; B is located in the center of the equilateral triangle composed of three oxygen atoms. In the unit cell structure, multiple [SrO6] octahedrons form the first layer, and [SnO6] octahedrons form the second layer. The two layers are connected by shared oxygen atoms at the vertices.
2. The preparation method according to claim 1, characterized in that: The pre-sintering of the mixed raw materials comprises: The mixed raw materials were placed in a sintering furnace, heated to 1000° C. at a heating rate of 5° C. / min and kept at that temperature for 10 hours to complete pre-sintering.
3. The preparation method according to claim 1, characterized in that: The step of adding the PVA aqueous solution to the sieved and dispersed mixed material, mixing the mixed material, granulating the mixed material, and pressing the mixed material to form a ceramic body comprises: The mixed material is passed through an 80-mesh sieve for dispersion treatment.
4. The preparation method according to claim 1, characterized in that: The mass fraction of the PVA aqueous solution is 5%, and the added amount of the PVA aqueous solution is 8wt% of the mass of the mixed material.
5. The preparation method according to claim 1, characterized in that: The ceramic body has a diameter of 12 mm and a height of 6 mm.
6. The preparation method according to claim 1, characterized in that: The step of sintering the ceramic green body after debinding the green body comprises: The ceramic green body after the debinding treatment is placed in a sintering furnace, and the temperature is raised to 1100° C. to 1200° C. at a heating rate of 5° C. / min and kept at this temperature for 8 hours to complete the sintering treatment.
7. A low dielectric constant borate microwave dielectric ceramic prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The chemical composition expression of the low dielectric constant borate microwave dielectric ceramic is SrSn(BO3)2, the dielectric constant of the low dielectric constant borate microwave dielectric ceramic is 5.42-6.12, the quality factor of the low dielectric constant borate microwave dielectric ceramic is 22142GHz-32618GHz, and the resonant frequency temperature coefficient of the low dielectric constant borate microwave dielectric ceramic is -48.31ppm / ℃-53.37ppm / ℃; the crystal structure of SrSn(BO3)2 ceramic is a layered structure composed of [SrO6] octahedron, [SnO6] octahedron and [BO3] plane triangle; B is located in the center of an equilateral triangle composed of three oxygen atoms, and in the unit cell structure, multiple [SrO6] octahedrons form the first layer, and [SnO6] octahedrons form the second layer, and the two layers are connected by sharing oxygen atoms at the vertices.
Citation Information
Patent Citations
Glass-free microwave dielectric ceramics and the manufacturing method thereof
CN101583579A